Clinical Relevance of Vitamins and Carotenoids With Liver Steatosis and Fibrosis Detected by Transient Elastography in Adults - Liu, Xiaohui; Shen, Hong; Chen, Mingfeng; Shao, Jun (Frontiers in Nutrition, 2021)
Background: Vitamins and carotenoids may be involved in the pathogenesis of nonalcoholic fatty liver disease (NAFLD). Previously related publications mainly focused on vitamin D and vitamin E, and studies on other vitamins and carotenoids and NAFLD are scarce. Methods: This study aimed to explore the clinical relevance of vitamin A, B vitamins (vitamin B1, vitamin B2, niacin, vitamin B6, folate, vitamin B12 and choline), vitamin C and carotenoids (α-carotene, β-carotene, β-cryptoxanthin, lycopene, lutein+zeaxanthin) with liver steatosis and fibrosis in the 2017-2018 NHANES (N=4,352). Liver steatosis and fibrosis were detected by transient elastography. Logistic regression, linear regression and restricted cubic splines were adopted to explore the non-linear dose-response relationships. Results: Higher intakes of vitamin C [0.68 (0.50-0.93)] and β-carotene [0.71 (0.54-0.93)] were inversely associated with liver steatosis. Higher levels of serum vitamin C [0.45 (0.32-0.62)] were inversely associated with liver fibrosis, while higher intakes of choline [1.43 (1.04-1.98)] and α-carotene [1.67 (1.01-2.74)] were positively associated with liver fibrosis. In addition, marginally inverse association between lutein+zeaxanthin and liver steatosis and positive association between vitamin B12 and liver fibrosis were found. In linear regression, the above-mentioned associations between vitamin C, β-carotene and lutein+zeaxanthin and liver steatosis, and serum vitamin C, choline, α-carotene and vitamin B12 and liver fibrosis were also found. The above-mentioned associations were mainly linear, while the relationship between β-carotene and liver steatosis might be non-linear. Conclusion: Vitamin C, α-carotene, β-carotene, lutein+zeaxanthin, choline and vitamin B12 may be associated with liver steatosis and fibrosis.